The Burkholderia Type VI Secretion System 5: Composition, Regulation and Role in Virulence - Lennings, Jan; West, T. Eoin; Schwarz, Sandra (Frontiers in Microbiology, 2019)
The soil saprophyte and Tier I select agent Burkholderia pseudomallei can cause rapidly fatal infections in humans and animals. The capability of switching to an intracellular life cycle during infection appears to be a decisive trait of B. pseudomallei for causing disease. B. pseudomallei harbors multiple type VI secretion systems (T6SSs) orthologs of which are present in the surrogate organism Burkholderia thailandensis. Upon host cell entry and vacuolar escape into the cytoplasm, B. pseudomallei and B. thailandensis manipulate host cells by utilizing the T6SS-5 (also termed T6SS1) to form multinucleated giant cells for intercellular spread. Disruption of the T6SS-5 in B. thailandensis causes a drastic attenuation of virulence in wildtype but not in mice lacking the central innate immune adapter protein MyD88. This result suggests that the T6SS-5 is deployed by the bacteria to overcome innate immune responses. However, important questions in this field remain unsolved including the mechanism underlying T6SS-5 activity and its physiological role during infection. In this review, we summarize the current knowledge on the components and regulation of the T6SS-5 as well as its role in virulence in mammalian hosts.